P1505COMORBIDITY AND AGE OF DIALYSIS PATIENTS OUTPERFORMS FRAILTY BURDEN AS A PREDICTOR FOR MORTALITY - Milenkova, Mimoza; Spasovska Vasilova, Adrijana; Canevska, Aleksandra; Pushevski, Vladimir; Selim, Gjulshen; Sikole, Aleksandar; Rambabova Bushljetikj, Irena; Trajcheska, Lada; Spasovski, Goce (Oxford University Press (OUP), 2020)
Abstract Background and Aims The life expectancy in dialysis patients depends on patients’ age and comorbidities. Frailty in elderly patients is a state of impaired homeostasis with loss of physiologic reserve and a consequent impaired responses to dialysis burden. In this study we assessed the impact of age, comorbidities and frailty on dialysis patients’ survival. Method The study enrolled 162 prevalent patients on chronic hemodialysis with mean dialysis vintage of 100 months, 55% were women and 21 % had diabetes. Patients were divided into three groups by the Khan Comorbidity index score, highest score was considered worse. Frailty was assessed by presence of 3 or more symptoms (unintentional weight loss, feeling exhausted, weak grip strength, slow walking speed and low physical activity) and expressed as absolute number. Estimates of five years life expectancy were assessed by Kaplan Meier survival log-rank test and Cox regression hazard model. Results There were 26 (16%) with lowest score, 85 (52%) with medium score and worst highest score in 51 (31%). During the 5 years of follow up 69(43%) patients died of all-cause mortality. There were no deaths in the group with lowest score and mortality rates in the intermediate and worse score group increased by double (0; 30%; 69%, respectively). Significantly higher mean life expectancy was found in lower Khan Score groups: 60mo; 48.40 ± 18.51; 32.44 ± 22.06, log-rank: p < 0.012. Patients that scored worse had four folds higher risk for death HR 4.2 (95% CI: 2.72 – 6.36), p=0.0001. In the multivariate model Khan Score was a more powerful predictor of mortality than frailty in elderly, with HR 3.2 (95% CI: 2.88 – 5.41), p=0.0001. Conclusion Comorbidities and age outperforms frailty burden as a predictor of mortality in dialysis patients.